Reasoning rights : comparative judicial engagement - Bowles, Nigel; Lazarus, Liora; McCrudden, Christopher (Hart Publishing, 2016)
"This book is about judicial reasoning in human rights cases. The aim is explore the question: how is it that notionally universal norms are reasoned by courts in such significantly different ways?"--Page i